Low-Profile Differentially-Fed Tightly-Coupled Dipole Array - Bobkov, I. N.; Yukhanov, Yu. V. (Izvestiâ vysših učebnyh zavedenij Rossii. Radioèlektronika, 2024)
Introduction. Tightly coupled dipoles currently belong to one of the most popular types of antenna arrays. Their main advantages include an electrically low-profile height, the ability to scan the beam across a wide sector of angles without the onset of scan blindness, and a low level of cross-polarization. In recent years, the number of publications on the topic of antenna arrays of this type has increased significantly. The authors have paid sufficient attention to baluns included in the antenna array elements. However, the possibility of implementing a differentially-fed scheme in antenna arrays of this type remains poorly studied. This makes the study of this subject especially relevant in the development of radio devices where such feed technique is preferable. Aim . Differentially-fed tightly-coupled dipole array design and study. Materials and methods. The following materials were used to create the prototype: copper sheet, ceramic glass substrate ST-50-1, dielectric RO3003. A numerical study of the characteristics was carried out in the ANSYS HFSS environment; an experimental study of the prototype was carried out in an anechoic chamber using an automated measuring complex and a vector network analyzer. Results. The results of designing a planar antenna array of tightly-coupled dipoles for the X-band are presented. In the antenna array, each of the dipole arms is fed using a separate coaxial cable, while the two arms of one dipole are fed out-of-phase. The results of a numerical study of the characteristics of an 8 × 8 antenna array made from the developed elements are presented. Across the range from 6.5 to 12.25 GHz, the average active VSWR does not exceed 3, while the gain varies from 21.5 to 25.7 dBi. The possibility of beam scanning in a sector of angles up to ±45° is shown. The results of an experimental study of the radiation characteristics and matching of the prototype of a single element are presented. Conclusion. The importance of taking into account the effects that arise at the edges of finite antenna arrays during simulations is shown. The feasibility of manufacturing and measuring antenna array prototypes with a large number of elements is experimentally confirmed. The proposed element design demonstrates the possibility of implementing the differentially-fed scheme in tightly coupled antenna arrays.